2022
DOI: 10.3390/nu14040767
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Practices among Adult Cancer Survivors Living on the Island of Ireland: A Cross-Sectional Study

Abstract: The purpose of this research was to explore the nutrition practices among post-treatment cancer survivors across Ireland. Cancer survivors aged 18+ years living across Ireland, who were not palliative and had completed active cancer treatment at least six months previous, were recruited to complete an online survey assessing dietary quality, food choice and satisfaction with food-related life as well as clinical and nutrition status. It was circulated by cancer support networks and on social media. Descriptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 47 publications
3
13
1
Order By: Relevance
“…First, one study showed that 95.2% of inpatients realized it was important to have good eating habits, such as eating more protein and low-fat food, as well as keeping up a good appetite to maintain enough intake. The result was higher than that of another study 59 from Iceland among adult cancer survivors. The probable reason could be that chemotherapy seriously affects the nutritional status of patients.…”
Section: Discussioncontrasting
confidence: 71%
“…First, one study showed that 95.2% of inpatients realized it was important to have good eating habits, such as eating more protein and low-fat food, as well as keeping up a good appetite to maintain enough intake. The result was higher than that of another study 59 from Iceland among adult cancer survivors. The probable reason could be that chemotherapy seriously affects the nutritional status of patients.…”
Section: Discussioncontrasting
confidence: 71%
“…There is currently a shortfall of oncology dietitians in Ireland, with one dietitian for every 4500 patients and limited to no service for survivors; these needs are not being met 41 . It should be noted that these figures are from 2019 and so staffing may have changed in the interim; however, lack of access to nutrition advice continues to be reported 42 , 27 . Similar findings have been reported in the UK, 43 Europe, 44 New Zealand 45 and the USA 22 .…”
Section: Discussionmentioning
confidence: 51%
“…Eligibility included adult cancer survivors (aged ≥18 years) who lived across Ireland and had completed active cancer treatment a minimum of 6 months previous to participating in this study. The participants were recruited as part of a more extensive quantitative study on the nutrition‐related life of Irish cancer survivors 20 . Surveys for the quantitative analysis were anonymous; however, participants had the option to express interest in participating in this qualitative study.…”
Section: Methodsmentioning
confidence: 99%
“…The participants were recruited as part of a more extensive quantitative study on the nutrition-related life of Irish cancer survivors. 20 Surveys for the quantitative analysis were anonymous; however, participants had the option to express interest in participating in this qualitative study. Prior to the focus groups, interested participants provided informed written consent.…”
Section: Participants and Recruitmentmentioning
confidence: 99%